The Legal Policy on Traffic Breaches by Children Under Age/Minors - Wahyu Lurus Stiyo Budi; Bambang Tri Bawono (Jurnal Daulat Hukum, 2020)
This study aims to explain the law enforcement mechanism against traffic violations by minors. To explain the implementation of law enforcement in relation to a sense of justice for the parties concerned. This study uses a normative juridical approach. This type of research is a case/field research. Case/field research is research that aims to study intensively the background of the current state and the environmental interactions of an object. So that analysis and facts can be obtained carefully, thoroughly, and clearly about the process of resolving cases of traffic violations against minors. The results showed that law enforcement against traffic violations by minors, namely through diversion, namely at the level of investigation, prosecution, and examination of cases of children in district courts must be pursued by Diversion, provided that the criminal act is committed; Is threatened with imprisonment for a maximum of 7 (seven) years and does not constitute a repeat offense. The criminal sanctions that are applied to traffic violations of minors, namely the judge's decision based on Act No. 3 of 1997 in the Juvenile Criminal Justice System Bill in the form of crimes or actions. the perpetrator is still subject to punishment for the incident through the applicable procedures according to the Juvenile Criminal Court Law.